Effectivity of Repetitive Transcranial Magnetic Stimulation Improving Depressive Symptoms and Motoric Strength Ischemic Stroke - RUNTUWENE, INNEKE MAGDALENA; Akbar, Muhammad; Kurnia Bintang, Andi; Tammasse, Jumraini; Muis, Abdul; Alfian Zainuddin, Andi (Faculty of Medicine, Hasanuddin University., 2023)
Introduction: Post-stroke depression often causes problems. Depression can slow motor recovery. Giving antidepressants takes one month, and thus Transcranial Magnetic Stimulation (TMS) was developed, especially repetitive Transcranial Magnetic Stimulation (rTMS). This study aims to assess the effectiveness of rTMS in improving depressive symptoms and motor strength in ischemic stroke patients. Methods: An experimental study with a randomized pretest-posttest control group design was conducted at Wahidin Sudirohusodo Hospital and a network hospital in Makassar from August to October 2022. The treatment group received standard therapy for ischemic stroke, antidepressants, and rTMS; the control group received standard therapy for ischemic stroke and antidepressants for ten days. In this study, the Hamilton Depression Rating Scale (HDRS) and the Medical Research Council (MRC) scale were used and measured in the treatment and control groups on the first and tenth days. Results: A total of 40 subjects met the criteria and were divided into a treatment group (n = 20) and a control group (n = 20). The HDRS score in the treatment group was smaller than in the control group. The value of left extremity motor strength in the treatment group was greater than that of the control group using the Wilcoxon Test. The correlation of the HDRS score to motor strength in the treatment and control groups showed a negative correlation of the HDRS score to the left extremity using the Spearman Test. Conclusions: rTMS effectively improves depressive symptoms and motor strength in ischemic stroke, given standard ischemic stroke therapy, antidepressants, and rTMS.